Estimation of human exposure to polycyclic aromatic hydrocarbons (PAHs) based on the dietary and outdoor atmospheric monitoring in the Czech Republic - Polachova, Andrea; Gramblicka, Tomas; Parizek, Ondrej; Sram, Radim J; Stupak, Michal; Hajslova, Jana; Pulkrabova, Jana (Environmental research, 2020)
In everyday life, humans can be exposed to various chemicals including ubiquitous polycyclic aromatic hydrocarbons (PAHs) mostly through food consumption and/or inhalation. In the presented study, we evaluated PAH concentrations in duplicate samples (n = 251). Concurrently, the outdoor concentrations of PM2.5-bound PAHs in filters (n = 179) were also monitored. The daily exposure to PAHs was subsequently estimated for the risk group of pregnant women living in two different cities (Most city and Ceske Budejovice city) in the Czech Republic. This is the first unique study in Europe to evaluate human daily exposure to 20 PAHs both from inhalation (outdoor air) and dietary intake. For the analysis of samples collected during the years 2016/2017, a gas chromatography coupled to tandem mass spectrometry was applied. Focusing on the diet samples, a slightly higher sum of detected PAHs was measured in duplicates obtained from the mothers living in the Most city (0.115-186 ng g-1) compared to the Ceske Budejovice city (0.115-97.1 ng g-1). This could be due to a higher occurrence of major analytes (pyrene, phenanthrene and fluoranthene) and the different composition of daily diet. The values of toxic and most often detected substance, namely benzo[a]pyrene (BaP), were also higher by 35% in the Most city. Regarding the outdoor air contamination (only particulate phase - PM2.5 was assessed), here the opposite situation was observed, relatively higher amounts of all PAHs were monitored in the Ceske Budejovice city (median: 2.22 ng m-3) than in the Most city (median: 1.07 ng m-3). These higher PAH concentrations in the Ceske Budejovice city are probably caused by more intense traffic, higher population and also by the occurrence of old-fashioned heating plant. Depending on a seasonal variability, especially during the cold season, the concentrations of BaP exceeded the European average emission limit (1 ng m-3) by 1.5-6 times. This highest inhalation exposure to all PAHs was observed in February. However, the dietary intake still represents the dominant contributor (>90%) to the total PAH exposure.
Keywords: monitorování životního prostředí; látky znečišťující vzduch; dieta; vystavení vlivu životního prostředí; Air Pollutants; Cities; těhotenství; Europe; Diet samples; Česká republika; Evropa; Risk Assessment; Environmental Monitoring; Environmental Exposure; polycyklické aromatické uhlovodíky; Czech Republic; Pregnant women; PAHs; ženské pohlaví; Total exposure; hodnocení rizik; Humans; Pregnancy; Polycyclic Aromatic Hydrocarbons; Air filters; plynová chromatografie s hmotnostně spektrometrickou detekcí; velkoměsta; Diet; Female; Gas Chromatography-Mass Spectrometry; lidé